1995
DOI: 10.1074/jbc.270.49.29541
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokine Responsive Vascular Smooth Muscle Cell Enhancer of Inducible Nitric Oxide Synthase

Abstract: The production of inducible nitric oxide synthase (iNOS) within vascular smooth muscle (VSM) cells following exposure to proinflammatory cytokines is a major cause of the vasorelaxation and hypotension of septic shock. We have defined the cytokine-responsive element of the murine iNOS promoter, transfected into a VSM cell line, and the role of the NF-kappa B/Rel family of proteins in iNOS gene activation in these cells. The combination of interleukin-1, interferon-gamma, and tumor necrosis factor-alpha stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(116 citation statements)
references
References 29 publications
2
113
0
1
Order By: Relevance
“…NF-B activation is a necessary factor in iNOS induction. 27,32 NF-B complex I (Figure 3) was remarkably induced in RASMC and macrophages and consisted of heterodimers of the p65 and p50 subunits (Figure 3 and 4). However, consistently, NF-B complex II and III were mainly induced in RASMC, and these bands appear to contain p50 and other subunits of NF-B (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-B activation is a necessary factor in iNOS induction. 27,32 NF-B complex I (Figure 3) was remarkably induced in RASMC and macrophages and consisted of heterodimers of the p65 and p50 subunits (Figure 3 and 4). However, consistently, NF-B complex II and III were mainly induced in RASMC, and these bands appear to contain p50 and other subunits of NF-B (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In macrophage cells, the downstream NF-B site at position Ϫ76 to Ϫ85 bp of the mouse iNOS promoter functions as a core promoter, 32,33 but the upstream NF-B site of the iNOS promoter plays an important role in eliciting responses to cytokines in the A7r5 rat smooth muscle cell line. 27 Similarly, when the iNOS promoter was transfected into cultured RASMC, a key region was located at Ϫ234 bp from the 5Ј-region. 28 Data have also demonstrated that LPS activation of the human iNOS promoter exhibits cell-type specificity.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 In vitro studies implicated that NF-B activation alone was fully responsible for induction of iNOS gene by lipopolysaccharide or cytokine in murine macrophages 41 and rat smooth muscle cell lines. 48 To evaluate the contribution of NF-B activation to con A-induced iNOS expression, PDTC, a highly selective inhibitor of NF-B, was used. 49 NF-B translocation was inhibited in PDTC-pretreated mice, indicating that NF-B is the main regulatory transcription factor in con A-mediated iNOS expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the downstream NF-kBd site (Ϫ85 to Ϫ76) was necessary for iNOS inducibility by LPS in a macrophage-like cell line (RAW 264.7) (7-9). Recently, cytokine regulation of the iNOS promoter/enhancer has also been investigated (27) in a clonal cell line originating from the thoracic aorta of embryonic rats (A7r5) (28). Using multiple cytokine stimulation (IL-1␤, tumor necrosis factor-␣, and interferon-␥), these investigators (27) reported the upstream NF-B site (Ϫ971 to Ϫ962) may play a role in the regulation of the iNOS 5Ј-flanking sequence in A7r5 cells.…”
Section: Fig 3 Mutation Of the Downstream Nf-b Site (Nf-bd) In The mentioning
confidence: 99%